REDUCTION OF NITRIC OXIDE WITH CARBONACEOUS MATERIALS FROM PEAT - Schultz, E. L.; Moreira, R. F. P. M.; José, H. J. (Revista de Engenharia Térmica, 2005)
The direct NO reduction to produce N2 and CO2 using carbonaceous materials, chars and activated carbons, was studied. Chars were prepared from peat by pyrolysis, at temperatures ranging from 873 K to 1073 K. Activated carbons were prepared by the physical activation of chars with steam, in a steel reactor, at 1073 K for 12 minutes, 25 minutes and 45 minutes. The kinetics of NO reduction using chars and activated carbons produced at different experimental conditions were evaluated at different temperatures in the range 623-723 K. The gaseous products were essentially CO2 and N2 and the amount of CO produced was negligible. The effect of the temperature on the kinetics of reduction was also evaluated and the relationship between the rate constant and the temperature showed an Arrhenius dependence. Activation energies of the NO reduction were in the range 6.75 to 7.97 kcal.mol-1 for the chars and in the range 8.14 to 9.52 kcal.mol-1 for the activated carbons.